Analisis Pelayanan Kemoterapi Peserta Badan Penyelenggara Jaminan Sosial di Rawat Singkat Anyelir Rumah Sakit Kanker “Dharmais” dengan Metode Lean Tahun 2015 - Julipriohadi, Agung (UI Scholars Hub, 2016)
Rumah Sakit Kanker “Dharmais” (RSKD) as a cancer referral centers nationwide in Indonesia, trying to implement a culture of continuous improvement. Lean methods provide analytical approach to the problem of organizing the queue chemotherapy participant of Badan Penyelenggaran Jaminan Sosial (BPJS), particularly in Anyelir ward (One Day Care). Cross-functional Flowchart, Value Stream Mapping, Fishbone diagram, and 5 Why's were used to show the situation and identify activities that Value Added and Non-Value Added based on the patient's perspective. With the proposed improvements, Projected Value Perfomance showed increased activity efficiency up to 43,1%, save the time up to 48%, and cut the mileage up to 71.8% of one patient in a day.